Error identification and improvement in English first additional language (EFAL) : a case study of Grade 10 essay writing - Maruma, Mamalatswa Walburga (Gender and Behaviour, 2017)
This paper seeks to identify errors committed by learners in EFAL essay writing, focussing on causes behind such errors, and strategies to eliminate them as a way of improving learners’ writing skills. Document review was adopted as the research method in this study. 15 Grade 10 essays from Mmapadi Secondary school were reviewed based on errors committed. The study revealed ten types of errors committed in EFAL Grade 10 essay writings. It revealed that learners’ use of technological devices is one of the main sources of spelling errors. It also revealed the following as sources of spelling errors:The interference of mother – tongue and partial learning in the target language.Inability to differentiate between spoken and written language. Not proofreading and carelessness. The paper recommends that learners should be given more practice on essay writing with intensive monitoring by teachers. Learners should be encouraged not to rely on technology for spelling rather encourage practice through dictation and spelling tests. The culture of reading should be cultivated in learners for writing proficiency.This leads to a conclusion that reading and writing skills practice under the guidance of skilful and experts teachers can improve learners’ writing competency.
Journal article published in the journal of Gender and Behaviour
Keywords: English First Additional Language; Writing Skills; Spelling Errors; Error Analysis; Mother Tongue Interference; English language -- Writing; English language -- Study and teaching -- South Africa; English language -- Spelling; Language and languages -- Study and teaching -- Error analysis; Native language